Pengaruh Antrian Kendaraan Di SPBU Maccorawalie Kabupaten Pinrang Terhadap Arus Lalu Lintas - Alfian Reski Saputra; Adnan Adnan; Andriyani Andriyani (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Maccorawalie Gas Station is one of the gas stations located in Pinrang. Regency, with an increase in the number of vehicles, it will automatically result in an increase in fuel demand as a result of fuel scarcity, causing motor vehicles owners to be able to queue for hours at public fuel filling stations. This Research aims to determine the length of queues that occur due to delays in fuel. supply and the level of service and arrival at the Maccorawalie gas station.Using quantitative research methods, using Model B Formula calculations: (M/M/S) (Multiple Line Queue Model). The research results show that the queue length that occurs due to delays in fuel supply at peak hours 10:00–11:00 WITA On Monday, 21 August 2023, is 44 meters, and on Thursday, 24 August 2023, is 12.75 meters, and on Saturday, August 26, 2023, namely 31.5 meters. The level of service on Monday, August 21 2023 is 3 vehicles per hour on Thursday, August 24. 2023, it is 8 vehicles/hour, and on Saturday, August 26, 2023, it is 4 vehicles/hour. The arrival rate on Monday, August 21, 2023, is 7 vehicles per hour.On Thursday, August 24, 2023, it is two vehicles per hour, and on Saturday, August 26.In 2023, it will be 5 vehicles per hour.